Reframing learner autonomy in Arabic language education for non-native speakers: a theoretical framework of power, control, and motivation - Almelhes, Sultan (Frontiers in Education, 2025)
Second language acquisition (SLA) has gradually shifted toward an emphasis on learner autonomy. If learners take responsibility for their own learning processes, they can achieve success. Thus, this article discusses how learner autonomy plays a role in SLA of Arabic to non-native speakers in the light of Foucault’s Discourse and Institutional Power, Bernstein’s Classification and Framing Theory, and Self-Determination Theory (SDT). The focus is on how activities during structured educational systems affect the nature of student engagement and motivation in connection with control over learning. The presentation of the discussion is based on empirical and theoretical studies that demonstrate that autonomy can shift teachers’ and students’ dynamics and also contribute to boosting learner motivation and language proficiency. Arabic language education as an area of focus is dedicated to sociocultural and religious dimensions as they connect with institutional structures. Based on the findings, the argument for adaptive teaching models, which allow for learner agency, sociocultural considerations, and interdisciplinary curriculum design, is presented.